2021
DOI: 10.1111/bjet.13161
|View full text |Cite
|
Sign up to set email alerts
|

Families' digital media use: Intentions, rules and activities

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 39 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Digital media involves the use of different service systems and up-to-date network technologies for the dissemination of information (Graziotin et al, 2014;Wu, 2020). Digital media is an umbrella term that encompasses components such as social media (e.g., Facebook and LinkedIn), smartphones or tablets, video, wikis, and search engines like Google (Bond et al, 2018;Eichen et al, 2021).…”
Section: Digital Mediamentioning
confidence: 99%
“…Digital media involves the use of different service systems and up-to-date network technologies for the dissemination of information (Graziotin et al, 2014;Wu, 2020). Digital media is an umbrella term that encompasses components such as social media (e.g., Facebook and LinkedIn), smartphones or tablets, video, wikis, and search engines like Google (Bond et al, 2018;Eichen et al, 2021).…”
Section: Digital Mediamentioning
confidence: 99%
“…Research has shown that parents use different types of mediation strategies [34,36,46,47] depending on their beliefs about digital technology [6,8]. The differences in the mediation method that is used are in accordance with the parents' positive or negative expectations of the digital media's effects on their children [34], cultural orientation [34,48], motive [49], own media use and skills, and family context variables [35]. The increased societal focus on academic readiness also affects parents' practices in encouraging the use of structured activities that are designed to promote academic results in preschool [9,49].…”
Section: Parent-child Interactions During Playmentioning
confidence: 99%
“…The differences in the mediation method that is used are in accordance with the parents' positive or negative expectations of the digital media's effects on their children [34], cultural orientation [34,48], motive [49], own media use and skills, and family context variables [35]. The increased societal focus on academic readiness also affects parents' practices in encouraging the use of structured activities that are designed to promote academic results in preschool [9,49]. Regarding the influence of the child's age and gender on parental mediation, studies have revealed differences that are related to the child's age group [50,51], but not to child's gender [51,52], especially in younger children.…”
Section: Parent-child Interactions During Playmentioning
confidence: 99%
“…In this context, radio and television media must keep pace with the times and make all-round adjustments if they want to firmly grasp the initiative of public opinion guidance and maintain their competitiveness [3][4]. Only in this way can the radio and television media better play their role of guiding public opinion and fulfilling their social public responsibility [5]. Digital media technology in the application of radio and television produced digital television technology, digital television wireless coverage is terrestrial digital television [6][7].…”
Section: Introductionmentioning
confidence: 99%